2020
DOI: 10.1186/s12950-020-00263-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia: A key feature of COVID-19 launching activation of HIF-1 and cytokine storm

Abstract: COVID-19, disease caused by the new coronavirus, SARS-CoV-2, appeared in the end of 2019 and was rapidly spread in most countries. This respiratory virus has different symptoms from moderate to severe, and results in lung pneumonia following acute respiratory distress syndrome (ARDS) and patient’s death in severe cases. ARDS is a severe form of acute lung injury that is caused by high inflammatory response of the innate immunity cells. Hypoxia is the common feature in the inflammatory sites with having various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 72 publications
(74 reference statements)
2
117
0
1
Order By: Relevance
“…While HIF-1α drives LPS-induced IL-1β [ 63 ], TNF, IL-12, and VEGF expression [ 64 ], HIF1α has been postulated to reduce VILI via A2B receptor regulation [ 65 , 66 ]. We have shown HIF-2α, and to a lesser extent HIF-1α, are involved in transcriptional regulation of the ARDS/VILI DAMP, eNAMPT, [ 64 , 67 , 68 ]. Our current studies demonstrate that HIF-1α and HIF-2α accumulation (elicited by PHD2 inhibition) to also significantly increase nm MYLK promoter activities with HIF-1α induction more rapid and HIF-2α induction more delayed.…”
Section: Discussionmentioning
confidence: 99%
“…While HIF-1α drives LPS-induced IL-1β [ 63 ], TNF, IL-12, and VEGF expression [ 64 ], HIF1α has been postulated to reduce VILI via A2B receptor regulation [ 65 , 66 ]. We have shown HIF-2α, and to a lesser extent HIF-1α, are involved in transcriptional regulation of the ARDS/VILI DAMP, eNAMPT, [ 64 , 67 , 68 ]. Our current studies demonstrate that HIF-1α and HIF-2α accumulation (elicited by PHD2 inhibition) to also significantly increase nm MYLK promoter activities with HIF-1α induction more rapid and HIF-2α induction more delayed.…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients with COVID-19 the interplay between systemic hypoxia (due to lung injury), ATH, and cyclic hypoxia lead to a canonical activation of HIF-1ɑ. The subsequent effect of HIF-1α (explained in section 3) might explain why obesity increases the risk of cytokine storm in COVID-19 infected patients ( Jahani, Dokaneheifard, and Mansouri 2020a ).…”
Section: Different Types Of Hypoxia and The Differential Release Of Hmentioning
confidence: 99%
“…The names and uses of the medications acting at each level have been discussed in Table 1 ( Jahani, Dokaneheifard, and Mansouri 2020b ). Despite the encouraging results of such drugs, there are no ongoing trials about their repurposing for the treatment of COVID-19 treatment.…”
Section: Development Of Therapeutic Targets For Hif Switchmentioning
confidence: 99%
“…Earlier studies have also revealed an alternative strategy of coagulation development during hypoxia by Toll-like receptors 3 (TLR3) mediated NF-κB/ AP-1 signalling in endothelial cells in response to the viral infections [ 89 ]. Hypobaric hypoxia mediates TF activation and deposition of fibrin via TLR3 signalling [ 76 ].…”
Section: Role Of Hypoxia Mediated Coagulation During Sars-cov-2 Infecmentioning
confidence: 99%